The Target Differences of Anti-Tumorigenesis Potential of Curcumin and its Analogues Against HER-2 Positive and Triple-Negative Breast Cancer Cells - Edy Meiyanto; Ulfatul Husnaa; Ria Fajarwati Kastian; Herwandhani Putri; Yonika Arum Larasati; Annisa Khumaira; Dyaningtyas Dewi Putri Pamungkas; Riris Istighfari Jenie; Masashi Kawaichi; Beni Lestari; Takashi Yokoyama; Jun-ya Kato (Tabriz University of Medical Sciences, 2021)
Purpose: The current study aims to evaluate the in vitro cytotoxic and cell migration effects of synthetic curcumin and its analogues on HER2 and nuclear factor kappa B (NFκB) pathways, as well as the in vivo inhibitory effect on cancer growth of metastatic breast cancer. Methods: Cell viability, protein expression, and protein localization were determined in vitro using MTT assay, western blotting, and immunofluorescence, respectively. Meanwhile, scratch wound healing assay and gelatin zymography were conducted to investigate the metastasis inhibitory effect. The in vivo anti-tumor ability was evaluated in xenograft mouse model using triple-negative breast cancer (TNBC) cells. Results: Curcumin, PGV-0, and PGV-1 exhibited cytotoxic effect against HER2-overexpressing breast cancer cells. Although PGV-1 showed the best activity in the single cytotoxic assay, curcumin showed the strongest synergism with doxorubicin. Curcumin and PGV-0 inhibited membrane localization of HER2. In contrast, PGV-1 neither inhibited localization nor decreased the expression of HER2, nonetheless showed the most potent inhibition against nuclear localization of p65 indicating the different mechanisms of curcumin, PGV-0, and PGV-1. Regarding cancer metastasis, curcumin and PGV-1 showed inhibitory activities against cell migration and inhibited MMP-2 and MMP-9 protein expression. Lastly, PGV-1 was more potent compared to curcumin to suppress the tumor formation of metastatic breast cancer xenograft model in nude mice. Conclusion: Overall, our study strengthens the potency of curcumin analogue, PGV-1, for treating several types of cancer, including metastatic breast cancer.